KAJIAN MISKONSEPSI SISWA MELALUI TES MULTIPLE CHOICE MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) PADA MATERI REAKSI REDUKSI OKSIDASI KELAS X MIPA SMAN 1 PONTIANAK - Nurlela Nurlela; Mawardi Mawardi; Tuti Kurniati (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThis study aimed to describe the student misconceptions and find out the cause of misconceptions MIPA class X SMAN 1 Pontianak. The method used is descriptive qualitative approach. The technique of taking informants using purposive sampling techniques so that the informant obtained, namely class X MIPA 5 and 6. The data collection techniques such as measurement results of diagnostic tests and interviews. Data collection tools in the form of Multiple Choice Tests using Certainty Of Response Index (CRI), which consists of 10 items with five alternative answers and guidance interview. Based on the analysis of research data shows there are misconceptions students. The results showed the highest percentage of misconceptions in the amount of 63.93% on indicators to distinguish the concept of oxidation and reduction in terms of incorporation and release of oxygen and misconceptions lowest percentage that is equal to 4.92% on the indicator to distinguish the concept of oxidation and reduction in terms of release and acceptance of electrons. The cause of the misconceptions of students caused by the fault of students that includes associative thinking students, preconception or early concept is wrong, intuition is wrong, and the ability of students but it is also caused by the teaching methods are boring and less varied and selfconfidence of students is too great when filling criteria CRI.Keywords: student misconceptions, misconceptions cause, reaction oxidation reduction